Sanctions by and against international organizations : common issues and current developments / edited by Giovanna Adinolfi, Alessandra Lang, Chiara Ragni. - Adinolfi, Giovanna; Lang, Alessandra; Ragni, Chiara (Intersentia, 2024)
This book examines the most recent practice related to the use of sanctions by and against international organizations. As its fundamental legal framework for investigation it uses, on the one hand, the outcomes of the work of the International Law Commission of the United Nations on the responsibility for international unlawful acts, and the law of international organizations, including European Union law, on the other. Sanctions By and Against International Organizations addresses the following critical issues: (One) the rationale underlying the use of sanctions, and the extent to which they may be deemed to be measures promoting the protection of collective interests of the 'community' concerned; (Two) the legal qualification of the measures at stake from the perspective of both public and private international law (as sanctions, countermeasures or retorsion and as overriding mandatory rules or factual circumstances which impede an economic transaction, respectively); (Three) the attribution of the measures to the different actors involved in the sanctioning process (organizations and/or member States); (Four) the legality of sanctions, especially those which are not provided for in the rules of the organizations, and their impact on the membership as a whole; and (Five) the identification of the legal regime(s) applicable to measures undertaken by states against organizations (treaty remedies, international responsibility, or general rules applicable in the relationship between organizations and their members).